Pengaruh Cross Selling dan Telemarketing Customer Service Terhadap Penjualan Produk Cicil Emas Pada BSI KCP Probolinggo Soetta - Muhammad Ilham Mileneo; Khusnik Hudzafidah; Agung Yatiningrum (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
This research was conducted on BSI KCP Probolinggo Soetta with the aim of knowing the effect of cross selling and telemarketing customer service on sales of gold installment products BSI KCP Probolinggo Soetta. The type of research used is descriptive quantitative, through independent (free) cross selling and telemarketing customer service variables and the dependent variable (tied) sales of gold installment products. The population in this study used were customers at BSI KCP Probolinggo Soetta. Samples were taken as many as 83 customers from a total population of 475. Sampling using incidental sampling technique. The data sources use: (1) primary data, (2) secondary data. Data analysis methods used include: descriptive statistics, validity and reliability testing, classical assumption testing, multiple linear regression, coefficient of determination (R Square) and partial hypothesis testing. The conclusion of the research from the partial test shows that cross selling and telemarketing customer service have an influence on the sale of gold installment products